2018
DOI: 10.1007/s00345-018-2291-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical teaching in urology: patient safety and educational value of ‘LIVE’ and ‘SEMI-LIVE’ surgical demonstrations

Abstract: PurposeTo evaluate the opinion of urologists and their audience regarding patient safety and educational value of live surgical demonstrations (LSD) and semi-live surgical demonstrations (semi-LSD).MethodsFollowing the ‘2017 Challenges in Endourology’ meeting, a survey addressing patient safety and the educational value of LSD and semi-LSD was disseminated online to all participants. Survey outcomes of LSD and semi-LSD were compared. ResultsAll 279 respondents attended both LSD and semi-LSD. Overall, 53% of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…‘As live surgical broadcasts’ are first filmed and then later commented on by the surgeon. When comparing live surgical broadcasts to ‘as live surgical broadcasts’, participants at the World Urology Conference in 2015 and 2019 regarded ‘as live surgical broadcasts’ as slightly better or at least non-inferior to live surgical broadcasts in terms of educational impact 9 10. These authors postulate that ‘as live surgical broadcasts’ provide the same educational advantages, but since the surgeon cannot be distracted by questions, they provide greater surgical safety and a calm working environment for the surgical team.…”
Section: Discussionmentioning
confidence: 99%
“…‘As live surgical broadcasts’ are first filmed and then later commented on by the surgeon. When comparing live surgical broadcasts to ‘as live surgical broadcasts’, participants at the World Urology Conference in 2015 and 2019 regarded ‘as live surgical broadcasts’ as slightly better or at least non-inferior to live surgical broadcasts in terms of educational impact 9 10. These authors postulate that ‘as live surgical broadcasts’ provide the same educational advantages, but since the surgeon cannot be distracted by questions, they provide greater surgical safety and a calm working environment for the surgical team.…”
Section: Discussionmentioning
confidence: 99%
“…Participants felt overall the education value was similar and a substantial percentage of the surgeons performing the LBSP reported that they felt that live surgery did not provide optimal circumstances for patient safety. Therefore, the authors advocated the use of more pre-recorded unedited videos [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recently performed survey by Legemate et al conducted at the 2017 Challenges in Endourology congress reiterated that attendees attribute LSEs and SLSDs the same learning experience, while a substantial percentage of surgeons who had performed LSDs stated patient safety may be jeopardized. Nevertheless, one-third of the responders would attend fewer SEMs if SLSDs were to replace LSDs [21]. This finding suggests that despite all technological progress and benefits of SLSDs, LSDs remain a popular tool for surgical education.…”
Section: Discussionmentioning
confidence: 99%